The aggregation of point defetc in dislocation-free silicon single crystals - Talanin, V.I.; Talanin, I.E.; Voronin, A.A.; Sirota, A.V. (Functional Materials, 2007)
The formation kinetics for grown-in microdefects nucleation centers in dislocation-free silicon single crystals has been considered. It has been demonstrated that the diffusion-controlled aggregation of point defects defines the process of grown-in microdefects formation. Decomposition of oversaturated solid-state solution follows two mechanisms, namely vacancy-type and interstitial-type. Decomposition of oversaturated solid impurity solutions occurs at temperatures near the crystallization front, while decomposition of oversaturated solid solutions of intrinsic point defects is induced by crystal cooling (at T < 1200°C). The good consistency between theoretical and experimental results proves the validity of the proposed model for point defects aggregation.